The associations between dietary advanced glycation-end products intake and self-reported infertility in U.S. women: data from the NHANES 2013–2018 - Tong, Lingxia; Zhang, Xiaohui; Chen, Jingsi; He, Huanying; Zhang, Wenzhuo; Wan, Zhongxiao; Zhang, Hong (Scientific reports, 2025)
Evidence suggest that dietary advanced glycation end products (AGEs) might exert harmful effects on female reproductive function. However, population-based studies exploring the associations between dietary AGEs intake and female infertility remain lacking. This studyaimed to determine the relationship between dietary AGEs intake and female infertility based on National Health and Nutrition Examination Survey (NHANES). A cross-sectional analysis of 2863 participants in the NHANES 2013–2018 were included. The dietary AGEs, i.e. Nε-(carboxymethyl)lysine(CML), Nε-(1-carboxyethyl)lysine (CEL), and Nδ-(5-hydro-5-methyl-4-imidazolon-2-yl)-ornithine (MG-H1) were estimated using the combination of ultra-performance LC-tandem MS dietary AGEs database and two 24-h dietary recall interviews. Multivariate Logistic regression analyses were adopted to explore the relationships between dietary AGEs intake and self-reported infertility risk. Compared to the lowest tertile, total dietary AGEs (P-trend = 0.089) and CML (P-trend = 0.032) in the upper tertile were positively correlated with female infertility, and the corresponding odds radios (ORs) (95% confidence interval (CI)) were 1.44 (1.01, 2.06) and 1.64 (1.10, 2.45) respectively. Subgroups analysis found that in participants with overweight and obese, each 1-SD increment in dietary AGEs, CML and MG-H1 level was associated with 18% (95% CI: 1-38%), 21% (95% CI: 1-46%), and 16% (95% CI: 0-36%) elevated risk of infertility. Elevated dietary AGEs intake was associated with the higher risk of infertility for female subjects, this positive association was more pronounced in women with excess body weight.